Increasing the nitrate-to-ammonium ratio improved plant growth and nitrogen uptake in pineapple seedlings - Ma, Haiyang; Liu, Siru; Zhao, Qiufang; Liu, Yanan; Song, Shuhui; Shi, Lei; Li, Huayong; Shi, Weiqi (Frontiers in Plant Science, 2026)
IntroductionPrevious studies indicate that the combined supply of both nitrate nitrogen (NO₃⁻) and ammonium nitrogen (NH₄⁺) is more beneficial for pineapple growth than the exclusive supply of either NO₃⁻ or NH₄⁺ alone. However, the optimal ratio of NO₃⁻:NH₄⁺ that maximizes pineapple growth remains to be fully elucidated, which limits the optimization of nitrogen fertilizer management in pineapple cultivation.MethodsUniform plantlets of Ananas comosus L. cv. Comte de Paris were subjected to hydroponic experiments with five NO₃⁻:NH₄⁺ ratios (0:100, 30:70, 50:50, 70:30, and 100:0) and a fixed total nitrogen concentration of 4 mM. The shoot and root growth characteristics, as well as carbon (C) and nitrogen (N) accumulation traits of pineapple plants, were systematically investigated. Additionally, the NO₃⁻ and NH₄⁺ uptake rates of roots were determined.ResultsCompared with other treatments, the NO₃⁻:NH₄⁺ ratio of 70:30 significantly increased total root length and surface area, and exhibited the highest NO₃⁻ uptake rate. With increasing nitrate proportions in the nitrogen supply, plant N uptake and the contents of chlorophyll a (Chl a) and chlorophyll b (Chl b) were significantly increased. Specifically, relative to the sole NH₄⁺ treatment (0:100), the 70:30 ratio treatment increased leaf area by 61.10%, leaf dry matter content by 24.40%, plant N accumulation by 19.49%, and plant C accumulation by 21.62%. Enhanced N uptake and photosynthetic pigment synthesis facilitated leaf area expansion, thereby promoting overall plant growth.DiscussionThese results indicate that a NO₃⁻:NH₄⁺ ratio of 70:30 is optimal for pineapple growth, as it effectively enhances both root and shoot development and improves C and N accumulation. This finding provides valuable insights for optimizing nitrogen fertilizer management strategies, which is crucial for promoting pineapple productivity in practical cultivation.